How to Govern the Boat People: The Case of Guangzhou Port from 1949 to 1958 - Yang Haiyuan, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The case study of how to govern the boat people can be a typical case on understanding how a nation-state can govern a mobile population. This paper is mainly focusing on how the nation-state’s power penetrated into waterside society. After the People's Republic of China was newly established, Guangzhou Port was flooded with many scattered and poorly managed civilian ships. The Chinese Communist Party and government adopted the Qing management of registering both boat and the owner’s information, aiming at controlling the total supplement and the need, to meet the government’s distribution policy. Due to the mobility of the transportation, the residence information of the boat people could be different from the berth port. The situation gradually changed in the middle 1950s, the place of residence and berth port gradually registered the same. Based on the system of controlling ships and ports, the government had established transportation cooperatives to build transportation management systems. To prevent boat people from leaving the port randomly, the shipping management department further implemented zoning management and redefined the navigation area. This article argues that the Chinese government can reform water transport market structure and invent the system of transport management to complete the construction of state power on waterside society.Received 14th June 2023; Revised 30th July 2023; Accepted 15th August 2023